2016
DOI: 10.4103/1119-3077.183236
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and outcome of cranial neuroendoscopic surgery in a resource constrained developing African country

Abstract: Highlighted are the myriad obstacles which interface the successful set up of neuroendoscopy service especially in resource-constrained settings. Endoscopic procedures become safer with experience and complications reduce significantly after a steep learning curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 22 publications
(30 reference statements)
0
28
0
Order By: Relevance
“…In the African context, the literature reveals a broad spectrum of POMRs, with rates ranging between 2.5% and 39.1% for an assortment of intracranial interventions and pathologies. 1,4,[13][14][15][16][17][18] This stands in sharp contrast to the trends observed in North America and Europe, where analogous intracranial surgical interventions have consistently manifested markedly reduced POMRs. [19][20][21][22][23] Notably, certain studies within these developed regions have even reported an absence of perioperative mortalities.…”
Section: Pom Rates (Pomr) In Lmics: a Report Of Global Incidencementioning
confidence: 98%
See 3 more Smart Citations
“…In the African context, the literature reveals a broad spectrum of POMRs, with rates ranging between 2.5% and 39.1% for an assortment of intracranial interventions and pathologies. 1,4,[13][14][15][16][17][18] This stands in sharp contrast to the trends observed in North America and Europe, where analogous intracranial surgical interventions have consistently manifested markedly reduced POMRs. [19][20][21][22][23] Notably, certain studies within these developed regions have even reported an absence of perioperative mortalities.…”
Section: Pom Rates (Pomr) In Lmics: a Report Of Global Incidencementioning
confidence: 98%
“…Notably, training programs emphasizing the technical facets of surgical interventions, such as neuroendoscopy, have been instrumental in mitigating postoperative complications. 4 Neurosurgical advancements in LMICs have greatly benefited from international collaborations. These alliances, especially with prominent global institutions, provide crucial monetary support, resources, and skill enhancement.…”
Section: Lowering Pomrs In Intracranial Surgeries In Lmics: Strategic...mentioning
confidence: 99%
See 2 more Smart Citations
“…LMICs carry most of the burden of neurosurgical diseases and do not have enough resources to meet the local neurosurgical needs [23,24], yet clinical guidelines are developed in high-income countries where the bur-den of disease and the resources available differ from those in LMICs. For example, the most prevalent neurosurgical diseases, traumatic brain injury, stroke, and epilepsy, occur mostly in LMICs [10] where there is a lack of resources, and patients face delays in seeking care, reaching care, and receiving care.…”
Section: Plain Language Summarymentioning
confidence: 99%